(untitled) (American Journal of Research in Humanities and Social Sciences, 2024)
The current objective of the research is to ascertain the prevalence of fraud among high school students, and to identify which areas are more conducive to the prevalence of fraud among students through the percentage obtained by the field according to the order. Research Limits School and History Teachers for High School at Day Schools for Diwaniyah Governorate and for School Year (2023-2024), in order to achieve the research objectives, the survey curriculum was used, and the scale was built in the final form after completing a condition of honesty, consistency and power was discriminatory, and its number of paragraphs (27) A paragraph, spread over three axes, and alternatives to answering each paragraph, were to a degree (Very large, large, medium, weak, very weak). The tool was applied to the members of the sample of 368 teachers and schools in Diwaniyah governorate and its district and district for the academic year (2023-2024). The SPSS was used to analyze the data, and the results were shown as follows: 1- The total sample responses received a percentage of up to 82.796%. This shows us that the degree of prevalence of secondary fraud received a large percentage.2- The research areas were arranged according to the effects obtained after the interpretation of the results, showing that the educational impact received a percentage up to (84.620%) which made it the first of the fields, while the second position became the share of social impact after achieving a ratio of up to (81.793%), and lastly the scientific impact was ranked third with a percentage (81.661%), and from the foregoing we showed that all the fields got a (large) degree of influence.